2008
DOI: 10.1007/s00259-008-0805-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of [11C]GB67 binding to cardiac α1-adrenoceptors with positron emission tomography: validation in pigs

Abstract: The present study offers a methodology for using [(11)C]GB67 as a radioligand to quantify human myocardial alpha(1)-ARs in clinical PET studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Additionally, due to the non-invasive technique of these imaging tools, their model and imaging approach can provide a means to evaluate the progression of HF and to quantify the temporal changes in flow and metabolism. In addition to the information provided on perfusion and metabolic outcomes, additional imaging could be applied to interrogate regional activation of critical receptors or enzymes within the myocardium, [24][25][26][27][28] neurohormonal changes, [29][30][31][32][33] along with regional changes in myocardial hypoxia, 34 apoptosis, 35,36 necrosis, 37 and fibrosis. 38 Unfortunately, the current study reported a high attrition (overall survival rate of 26%) with a major cause of death attributable to lethal arrhythmias during the perioperative period.…”
Section: See Related Article Pp 655-665mentioning
confidence: 99%
“…Additionally, due to the non-invasive technique of these imaging tools, their model and imaging approach can provide a means to evaluate the progression of HF and to quantify the temporal changes in flow and metabolism. In addition to the information provided on perfusion and metabolic outcomes, additional imaging could be applied to interrogate regional activation of critical receptors or enzymes within the myocardium, [24][25][26][27][28] neurohormonal changes, [29][30][31][32][33] along with regional changes in myocardial hypoxia, 34 apoptosis, 35,36 necrosis, 37 and fibrosis. 38 Unfortunately, the current study reported a high attrition (overall survival rate of 26%) with a major cause of death attributable to lethal arrhythmias during the perioperative period.…”
Section: See Related Article Pp 655-665mentioning
confidence: 99%